2022
DOI: 10.3390/vetsci9080386
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Ehrlichia canis GP19 Protein as a Promising Vaccine Prototype Providing a Protective Immune Response in a Mouse Model

Abstract: The intracellular bacterium Ehrlichia canis is the causative pathogen of canine monocytic ehrlichiosis (CME) in dogs. Despite its veterinary and medical importance, there is currently no available vaccine against this pathogen. In this study, the recombinant GP19 (rGP19) was produced and used as a recombinant vaccine prototype in a mouse model against experimental E. canis infection. The efficacy of the rGP19 vaccine prototype in the part of stimulating B and T cell responses and conferring protection in mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Conventional immunoblotting approaches have helped identify major antibody reactive proteins from E. chaffeensis and E. canis , including major outer membrane proteins (OMPs) ( Ohashi et al., 1998a ; Ohashi et al., 1998b ), tandem repeat proteins (TRPs) ( Doyle et al., 2006 ; McBride et al., 2007 ; Luo et al., 2008 ; Luo et al., 2009 ; McBride et al., 2011 ) and ankyrin repeat proteins (Anks) ( Nethery et al., 2007 ; Luo et al., 2010 ), that contain linear antibody epitopes. Many of these proteins elicit protective immune responses in Ehrlichia infection models ( Li et al., 2001 ; Crocquet-Valdes et al., 2011 ; Kuriakose et al., 2012 ; Nambooppha et al., 2022 ). Moreover, experimental studies have demonstrated protection against infection using live-attenuated vaccines and subunit vaccines ( Rudoler et al., 2012 ; McGill et al., 2016 ; Budachetri et al., 2022 ); however, there are no commercial human or veterinary vaccines available for HME or CME.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional immunoblotting approaches have helped identify major antibody reactive proteins from E. chaffeensis and E. canis , including major outer membrane proteins (OMPs) ( Ohashi et al., 1998a ; Ohashi et al., 1998b ), tandem repeat proteins (TRPs) ( Doyle et al., 2006 ; McBride et al., 2007 ; Luo et al., 2008 ; Luo et al., 2009 ; McBride et al., 2011 ) and ankyrin repeat proteins (Anks) ( Nethery et al., 2007 ; Luo et al., 2010 ), that contain linear antibody epitopes. Many of these proteins elicit protective immune responses in Ehrlichia infection models ( Li et al., 2001 ; Crocquet-Valdes et al., 2011 ; Kuriakose et al., 2012 ; Nambooppha et al., 2022 ). Moreover, experimental studies have demonstrated protection against infection using live-attenuated vaccines and subunit vaccines ( Rudoler et al., 2012 ; McGill et al., 2016 ; Budachetri et al., 2022 ); however, there are no commercial human or veterinary vaccines available for HME or CME.…”
Section: Introductionmentioning
confidence: 99%